Dirâsah Tahlîliyyah Nahwiyyah ‘an Adawât al-Syarti wa Isti’mâluhâ fî al-Lugah al-‘Arabiyyah - Zullkiflih Zulkiflih; M Napis Djuaeni; Hamzah Hamzah (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2021)
This research is entitled Dirasah Tahliliyah Nahwiyyah 'an Adawat al-Syart wa Isti'maluha fi al-Lughah al-Arabiyyah (a grammatical analytic study of adhawat al-syart and its use in Arabic). This study aims to explain the essence of the syartiyah sentence and find out the use of adawat syart in Arabic. This study uses a qualitative approach with the type of library research. The method of collecting data is through documentation by using quotes and transferring trusted sources either directly or indirectly. The data analysis process goes through three interactive stages, namely data reduction, data exposure, then verification and drawing conclusions. The result of this study is that the syartiyah sentence is a sentence consisting of fi'il syart and jawabu syart by using adawat syart (devices of syart). Adawat syart is a set of tools used to form syartiyah sentences (fi'il syart and answer syart), which are divided into two types, namely adawat syart al-jazimah and adawat syart ghair al-jazimah. The mention of adawat (adawat syart) is because not all of them are in the harf category, but some are in the isim category, namely: in, idzma, man, ma, mahma, mataa, aina, ayyaana, annaa, haitsuma, ayyu, idza, kaifama, law, lawma, lawla and amma.